Therapeutic Response and Antifungal Susceptibility to Fluconazole in Women with Vulvovaginal Candidiasis - Zahra Vahedpoor; Mohammad Javad Azadchehr; Taha Baghbani; Tayebeh Felfelian Fini; Mehdi Nazeri (پیاورد سلامت, 2022)
Background and Aim: Vulvovaginal candidiasis (VVC) is a vaginal fungal infection that mainly caused by Candida albicans. Among various treatments and their controversial outcomes, oral fluconazole has been accepted as a common and efficient treatment for acute and chronic cases. The aim of this study is about therapeutic effect of fluconazole and evaluation of its antifungal susceptibility. Materials and Methods: In this cross-sectional study Samples were collected from 107 suspected patients to vulvovaginal candidiasis who went to the gynecology clinic of Kashan University of Medical Sciences in (2020-2022). At first consent and then demographic registrations were obtained. All samples were collected and cultured on Chromagar and Sabouraud’s dextrose agar and incubated at 30°C for 72 h. Yeast colonies were identified based on their colors and morphologic criteria. All patients were treated by a single dose of fluconazole (150 mg/ml) or two continuous additional doses, depending on the absence or history of recurrence. Improvement of clinical and mycological symptoms in patients were followed for 30-35 days. Antifungal susceptibility to fluconazole was determined by microdilution method (CLSI, document M27-A3). Results: A total of 107 patients were diagnosed with vulvovaginal candidiasis. Candida albicans (79.4%) was the most common identified species. total response to fluconazole treatment based on mycological findings (negative culture and direct smear) was 62.6% (P=0.012), there was no significant difference between candida species, albicans (64.7%) and non-albicans (54.5%), type of vaginal candidiasis forms (recurrent and non-recurrent) and antifungal susceptibility to fluconazole (MIC≤8)(P>0.05). Consideration of MICs≤1 and MICs>1 as a cutoff point there was a significant difference between failure and response to treatment (P=0.014). Conclusion: According to empiric treatment of Vulvovaginal candidiasis, concurrent Laboratory diagnosis with anti-fungal susceptibility could help us in selecting the appropriate treatment protocol and prevent the emergence or increase of resistant species.